The Effect of STAD Cooperative Learning Model and Critical Thinking Ability on Learning Outcomes PPKn Grade V Students of SD Negeri 060934 Medan Johor - Romaida Karo Karo; Reh Bungana Br Perangin-Angin; Abdul Murad (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to determine the differences in student learning outcomes taught by the cooperative learning model type STAD and conventional teaching, to find out the differences in the learning outcomes of PPKn students who have higher critical thinking skills compared to students who have low critical thinking skills, and to find out whether there is an interaction between the STAD type cooperative learning model with critical thinking skills on the learning outcomes of PPKn grade V students of SD Negeri 060934 Medan Johor. This research was conducted at SD Negeri 060934 Medan Johor. The research sample was determined by cluster random sampling, one class as an experimental class was taught with a STAD type cooperative learning model and one control class was taught conventionally. The sample to be studied amounted to 52 students consisting of 25 experimental class students and 27 control class students. Critical thinking ability tests are conducted to classify students who have high critical thinking skills and low critical thinking skills. Data were analyzed using two-way ANAVA using statistical tests with factorial design of 2x2 ANAVA with a significance level of > 0.05. Previously performed the normality test and homogeneity test analysis. The results showed that the learning outcomes taught using the STAD type cooperative learning model are better than conventional learning models in improving PKn learning outcomes of students as well as students who have high critical thinking skills who obtain better learning outcomes than students who have low critical thinking skills.